MODEL EVALUASI PEMBELAJARAN PAI UNTUK MENYELARASKAN DENGAN PERUBAHAN KURIKULUM DAN KEBUTUHAN SISWA DI ERA DIGITAL - , Ghozali; Edi Junaidi Ds; Abdul Bashith (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education (PAI) has a very important role in shaping the character and noble morals of PAI students not only to transfer religious knowledge, but also to instill moral and spiritual values ​​that are expected to be applied in everyday life. The purpose of this study is to evaluate the curriculum that continues to develop in the digital era, demanding an adaptive and relevant Islamic Religious Education (PAI) learning evaluation system to the needs of today's students, to develop an PAI learning evaluation model that is able to align the demands of the latest curriculum with the characteristics and needs of students in the digital era. The research method used is qualitative-descriptive with a literature review as the main method. The results of the study indicate that PAI learning evaluation needs to integrate technology-based approaches, such as the use of digital platforms, online assessments, and interactive and participatory evaluation methods. The results of this study are to develop PAI learning evaluation in the digital era to increase the effectiveness of learning, strengthen the internalization of religious values, and shape students' character holistically in accordance with the challenges of the digital era.